Designing principles of the Intelligent information technology for organization decisions - Ilyina, E.P.; Sinitsyn, I.P.; Yablokova, T.L. (PROBLEMS IN PROGRAMMING, 2017)
The functional structuring principles were proposed for the special kind of the organization decisions support systems which were named as the Intelligent information technologies. The features of such a system are as follows: support of ontologically integrated corporate knowledge about decisions in organization; intelligent mechanisms for compromises decision making under different viewpoints involving; consulting on all stages of the decision making process. The functional architecture model, information structure and the set of intelligent operations are characterized.